The Relationship between the Pre-Service Science Teachers’ Self-Efficacy towards Science Teaching and Tendency to Use Technology in Classes - Atilla Temur; Alper Durukan; Huseyin Artun (Mimbar Sekolah Dasar, 2022)
The effectiveness of science instruction undoubtedly relies heavily on the teacher. Moreover, international guidelines for science teacher training and the standards for their competencies emphasize the adequate utilization of instructional technologies. In this light, sophisticated instruction of science demands a teacher who has a high self-efficacy perception and is fluent in the use of instructional technology during the classes. Given these motives, this quantitative correlational study examined the relationship between senior pre-service science teachers’ self-efficacy perceptions towards teaching science and their tendency to use technology in class. The study sample consisted of 91 undergraduate students enrolled in the Science Education program of a state University in the Eastern Anatolian region of Turkey. The data was collected using two Likert-type scales subjected to Pearson Correlation analysis. The findings implied a positive, although the relatively weak linear relationship between the tendency to use technology in class and self-efficacy perceptions towards teaching science. Moreover, the calculated coefficient of determination value implies that either of the factors only infers 8% of the total variance of self-efficacy tendency to use technology. Finally, the implications and potential underlying factors affecting this relationship are discussed.